EVALUASI KINERJA BADAN LINGKUNGAN HIDUP DAERAH ISTIMEWA YOGYAKARTA DENGAN PENDEKATAN EMPAT PERSPEKTIF DALAM BALANCED SCORECARD - , AURA RAHMAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study evaluate the performance of BLH DIY using four perspectives in the balanced scorecard. Using the financial reports, performance reports, and primary data obtained from BLH DIY employees and people assisted by BLH DIY with questionnaires and interviews, the results showed that the performance of BLH DIY from a financial perspective, learning and growth perspective, internal process perspective, and customer perspective has been better. But there are few things that need attention, lack of internal networks that connect between computers, the number of coli bacteria that exceed the limits of tolerance, and the relationship between BLH DIY and people assisted by BLH DIY after development process which is less satisfactory.